Quantitative ethno-gynecological survey of traditional medicinal plants from Punjab province, Pakistan - Zareef, Huma; Sarim, Fazli; Qureshi, Rahmatullah (Ethnobotany Research and Applications, 2023)
Background: The purpose of the present study was to document quantitative indigenous knowledge of medicinal plants used for treating various gynecological disorders by the herbalist (Hakeem) and traditional communities of selected rural areas of Punjab, Pakistan. Materials and Methods: The study was conducted from February 2022 to January 2023. During the research work, the use of medicinal plants and their medicinal uses for curing gynecological disorders were recorded by interviewing 600 informants of different age groups (20-85 years) via semi-structured interviews. Results: In all, 60 therapeutic plants belonging to 15 families were recorded that were used by the traditional communities of study areas for the cure of various kinds of gynecological disorders. Among families, Asteraceae was the largest that contributed 17 species. The dominant life form was herbs (39 species) and the mostly used plant part was whole plant (14 species). The highest Relative Frequency Citation (RFC) was recorded for Anethum graveolens (0.96). Similarly, the highest Use Value (0.98) was recorded for Amaranthus caudatu,s Amaranthus angustifolius and the lowest (0.33) for Justicia adhatoda. Likewise, the highest Fidelity Level (FL) was recorded for Anaphalis nepalensis (100%) which was used to treat leucorrhea, and the lowest FL was recorded for Oxystelma esculentum (41.94%) in treating gonorrhea. Family importance index (FIV) indicated that Asteraceae was the dominant (96.66) in the region for contributing medicinal plants, while Zingeberaceae was the lowest one (16.66). Conclusions: The selected sites being remote areas are devoid of basic health facilities, so the natives learnt about medicinal plants to treat human diseases including gynecological problems. The current research work illustrated that the inhabitants have good knowledge about native plants for treating gynecological disorders. This research can be used as a benchmark for future pharmacological studies to discover novel herbal medicines. Keywords: Folk knowledge, Quantitative, Medicinal plants, Gynecological disorders, Punjab, Pakistan